EXPLORING THE INTERSECTION OF FINANCIAL DISTRESS, MARKET DIVERSIFICATION FAILURES, AND RISKY FINANCING: A CASE STUDY OF PT SRITEX’S DECLINE - Prana, Indra; Erri, Dirgahayu; Tambunan, Diana; Dewi, Intan Kusuma (Universitas Muhammadiyah Tangerang, 2025)
This study analyzed financial distress prevention efforts at PT Sritex using three prediction models: Springate S-Score, Zeta Score, and Discriminant Analysis. The results show the company is in a high-risk condition based on all three models. The Springate S-Score (0.78 < 1.0) indicates operational inefficiencies, the Zeta Score (1.5 < 1.81) indicates a risk of short-term bankruptcy, and the Discriminant Score (0.45 < 1.0) reflects financial instability. The analysis concluded that this condition could be prevented through strategic measures, including cost efficiency, debt restructuring, market diversification, and strengthening governance. Springate emphasizes working capital improvements, Zeta Score points to optimizing debt structures, while Discriminant Analysis suggests improving financial ratios. These findings form the basis for recommendations for management to improve transparency and risk management to mitigate bankruptcy. The research makes a practical contribution to stakeholders in developing evidence-based financial recovery strategies.